Procoagulant Properties of Intravenous Staphylokinase Versus Tissue-Type Plasminogen Activator - Okada, K; Lijnen, H R; Moreau, H; Vanderschuere, S; Collen, D (Thrombosis and Haemostasis, 1996)
The fibrin-specificity and procoagulant effects of recombinant staphylokinase (Sak42D) were compared with those of recombinant tissue-type plasminogen activator (rt-PA) in patients with acute myocardial infarction. Plasma samples were obtained at baseline and at 25 and 90 min, from 24 patients who were randomly assigned to a double bolus (15 mg each, 30 min apart) administration of Sak42D or to accelerated weight-adjusted rt-PA (maximum of 100 mg over 90 min). Baseline levels of fibrinopeptide A (FPA), prothrombin fragment 1+2 and thrombin-antithrombin III complex (TAT) were comparable in the Sak42D and rt-PA groups (p ≥ 0.6). In patients treated with Sak42D, plasma levels of FPA, prothrombin fragment 1+2 and TAT did not markedly increase during treatment (p = 0.06, p = 0.4 and p = 0.03, respectively). In contrast, during administration of rt-PA the levels of FPA, prothrombin fragment 1+2 and TAT increased significantly over baseline (p = 0.003, p < 0.0001 and p = 0.001, respectively). As a result, the levels of all three procoagulant parameters were significantly lower during treatment with Sak42D as compared to rt-PA. Thus, FPA levels in the Sak42D group (median values) were 40 ng/ml at 25 min and 11 ng/ml at 90 min, as compared to 88 ng/ml and 50 ng/ml in the rt-PA group (p = 0.0007 and p = 0.009, respectively). Prothrombin fragment 1+2 levels in the Sak42D group were 1.3 nM at 25 min and 1.2 nM at 20 min, as compared to 11 nM and 5.3 nM in the rt-PA group (both p < 0.0001). TAT levels were 4.7 ng/ml at 25 min and 6.2 ng/ml at 90 min in the Sak42D group, with corresponding values of 16 ng/ml and 9.6 ng/ml in the rt-PA group (p = 0.02 and p = 0.03, respectively).In the patients treated with Sak42D, no significant systemic fibrinolytic activation was observed, as revealed by unaltered levels of clotta-ble fibrinogen, plasminogen and a2-antiplasmin up to 90 min after the start of therapy. In contrast, the corresponding residual levels at 90 min in patients treated with rt-PA decreased to (mean ± SEM; n = 12) 62 ± 6%, 45 ± 5% and 52 ± 10%, respectively (all p < 0.01 versus the Sak42D group)These data confirm the high degree of fibrin-specificity of Sak42D and demonstrate that this is associated with significantly less generation of procoagulant activity in plasma after intravenous administration in patients with acute myocardial infarction